Potencial antimicrobiano e mecanismo de ação do óleo essencial de folhas de Ocimum gratissimum (Linn.) sobre espécies de Candida - Oliveira, Luciana de Brito Siebra e (2015)
Ocimum gratissimum (Linn.) is a medicinal plant popularly known as “wild basil” widely used in folk medicine. The plant has numerous compounds, and eugenol is the major constituent of its essential oil and likely the responsible for its antimicrobial activity. The aim of this study was to determine the antimicrobial activity and the mechanism of action of the essential oil extracted from the leaves of O. gratissimum L. (OEOg) against standard strains of Candida. The chemical characterization of OEOg constituents was performed by gas chromatography coupled to mass spectrometry (GC-MS). To evaluate the antimicrobial activity of OEOg the Minimum Inhibitory Concentration (MIC) was determined. The effect of time of exposure to OEOg and commercial antifungals, the modulating effect of OEOg in antifungal (ATF) activity for clinical use and the effects of the OEOg on different growth phases of Candida spp were another performed assays. The mechanism of action of OEOg was analyzed by the uptake of crystal violet test and the evaluation of microbial morphology by microculture of yeast technique. The effect of OEOg on red blood human cells was also evaluated. Eight standard strains of Candida were used to perform the assays: Candida albicans ATCC 10231; Candida albicans ATCC 44858; C. albicans ATCC 64124; C. albicans ATCC 90028; C. albicans ATCC 90029; Candida parapsilosis ATCC 90018; Candida tropicalis ATCC 750; Candida tropicalis ATCC 13803. OEOg was able to inhibit the growth of the strains C. albicans ATCC 10231 (MIC = 1,25 mg/mL), C. albicans ATCC 64124 (MIC = 0,625 mg/mL), C. parapsilosis ATCC 90018 (MIC = 1,25 mg/mL), C. tropicalis ATCC 13803 (MIC = 1,25 mg/mL), being able to reduce the growth rate of strains of Candida after 24 hours of exposure. For the OEOg-ATF associations, it was found a predominance of indifferent and antagonistic effects to Candida strains tested. The OE was able to positively modulate the action of ketoconazole against C. tropicalis ATCC 13803. OEOg was able to reduce the number of viable cells at all stages of microbial growth. The OEOg was able to promote a slight increase in uptake of crystal violet and caused changes in the ultrastructure of yeast, suggesting that its action target is the cell envelope. OEOg was slightly toxic to red blood human cells. The results showed that the OEOg has good activity against Candida yeasts, and its mechanism of action is possibly related to damage in the cell envelope. It has been observed low toxicity on human erythrocytes indicating that the “wild basil” is a promising plant for the development and elaboration of a new drug with potential activity for the treatment of fungal diseases, needing additional studies.